2020
DOI: 10.1371/journal.pone.0241901
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mechanical vibration down-regulates pro-inflammatory and pro-fibrotic signaling in human vocal fold fibroblasts

Abstract: Introduction Voice rest following phonotrauma or phonosurgery has a considerable clinical impact, but clinical recommendations are inconsistent due to inconclusive data. As biopsies of the vocal folds (VF) for molecular biology studies in humans are unethical, we established a new in vitro model to explore the effects of vibration on human vocal fold fibroblasts (hVFF) in an inflammatory and normal state, which is based on previously published models. Methods By using a phonomimetic bioreactor we were able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
1
6
0
3
Order By: Relevance
“…Dass von diesen Zellen u. a. mehr Kollagen und weniger Hyaluronsäure produziert wird, ist das morphologische Korrelat der SL-Narbe [ 27 ]. Ergebnisse der In-vitro-Versuche der Autor(inn)en zeigten, dass eine unmittelbare mechanische Aktivierung nach inflammatorischem Stimulus zu einer niedrigeren Expression inflammatorischer und fibrotischer Gene führten [ 28 ]. Auch Geschlechtsunterschiede in der ECM-Komposition stehen im Verdacht, Auswirkungen auf die Häufigkeit von SL-Veränderungen zu haben: Die Lamina propria von Männern weist mehr Hyaluronsäure als die von Frauen auf, wodurch ein stärkerer Schutz vor Phonotraumen ausgehen könnte [ 29 ].…”
Section: Mikrophysiologie/pathophysiologieunclassified
See 2 more Smart Citations
“…Dass von diesen Zellen u. a. mehr Kollagen und weniger Hyaluronsäure produziert wird, ist das morphologische Korrelat der SL-Narbe [ 27 ]. Ergebnisse der In-vitro-Versuche der Autor(inn)en zeigten, dass eine unmittelbare mechanische Aktivierung nach inflammatorischem Stimulus zu einer niedrigeren Expression inflammatorischer und fibrotischer Gene führten [ 28 ]. Auch Geschlechtsunterschiede in der ECM-Komposition stehen im Verdacht, Auswirkungen auf die Häufigkeit von SL-Veränderungen zu haben: Die Lamina propria von Männern weist mehr Hyaluronsäure als die von Frauen auf, wodurch ein stärkerer Schutz vor Phonotraumen ausgehen könnte [ 29 ].…”
Section: Mikrophysiologie/pathophysiologieunclassified
“…Die Arbeitsgruppe der Autor(inn)en hat in den letzten Jahren Protokolle entwickelt, mit welchen sie Epithelzellen und Fibroblasten aus laryngealer Mukosa isolieren, charakterisieren und kultivieren kann [ 28 , 33 , 41 ]. Ein weiterer wesentlicher Fortschritt war die Entwicklung geeigneter Zellkulturapparate, die die SL-Vibrationen auch unter Kulturbedingungen applizieren können.…”
Section: Ausblickunclassified
See 1 more Smart Citation
“…Vibrations also apply in regenerative medicine in bioreactors that mimic the natural environment for cell culture or stimulate cell differentiation [ 14 , 15 , 48 , 49 ]. Previous research findings showed that vibrations could affect stem cell behaviors and lead to the production of mature tissue [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, unregulated inflammatory response is shown to be an adverse event in the vocal fold. The molecules involved in the inflammatory response in the vocal fold have been extensively studied for at least a decade [ 23 , 24 ]. The consistency of studies in quantifying IL-1β, NF-ĸB, tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), transforming growth factor-beta (TGF-β), cyclooxygenase (COX2), HA and procollagen expression indicated that these molecules are closely related to inflammation in the vocal fold [ 25 ].…”
Section: Introductionmentioning
confidence: 99%